IMPLEMENTATION OF THE MERDEKA CURRICULUM THROUGH THE APPLICATION OF THE PROJECT-BASED BLENDED LEARNING MODEL IN MATHEMATICS LEARNING: IMPLEMENTASI KURIKULUM MERDEKA MELALUI PENERAPAN MODEL PROJECT-BASED BLENDED LEARNING DALAM PEMBELAJARAN MATEMATIKA - Nurhidayah, Nurhidayah; Yahya, Amran (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
This study aims to determine the effect of the implementation of the project-based blended learning model on improving students' mathematics learning outcomes as the implementation of the independent curriculum in mathematics learning. The research method used is quasi-experimental which consists of an experimental class and a control class. The experimental class applied the project-based blended learning model in learning mathematics, and the control class did not use the project-based blended learning model in learning mathematics. The instrument used is the test of students' mathematics learning outcomes given before and after the implementation of learning. The data analysis used was descriptive statistical data analysis and inferential statistical data analysis which consisted of the normality test, homogeneity test, and independent sample t-test for hypothetical testing using the N-gain value. The results of the data analysis show that the significance obtained is 0.000 <0.05 or in other words, H0 is rejected, so it can be concluded that there is a significant effect of applying the project-based blended learning model to improving students' mathematics learning outcomes.